Photoluminescence, electrical properties and electron band structure of (Ho, Yb)3+ co-doped SrBi4Ti4O15 multifunctional ceramics. Issue 7 (1st April 2022) - Zhang, Yuying; Duan, Lusheng; Zhang, Anqi; Wang, Da; Chu, Ruiqing; Xu, Zhijun; Li, Guorong; Zhang, Chao
Abstract: SrBi3.992- x Ho0.008 Yb x Ti4 O15 ( x = 0.000, 0.002, 0.004, 0.006, abbreviated as SBHT- x Yb) multifunctional ceramics were fabricated by solid-phase reaction method. Their electrical, luminescence properties and electronic band structure were investigated. At x = 0.002, samples exhibit enhanced piezoelectric coefficient ( d 33 = 19 pC/N) and optimal thermal stability. Thermal annealing behavior shows that the d 33 of SBHT-0.002 Yb at 460 °C remains 84% of its d 33 value at room temperature (RT). Excited by 980 nm laser, the SBHT- x Yb samples show two emission bands. Green emission at 548 nm and red emission at 658 nm are considered to be the transfer of two excited states 5 S2 and 5 F5 to the ground state 5 I8 of Ho 3+ ions, respectively. Furthermore, the electron band structure of SBHT- x Yb ceramics was calculated using density functional theory (DFT). It is found that the energy consumed for electron transition first decreases and then increases, while the 4 f orbital contributions of (Ho, Yb) 3+ ions are enhanced by doping with Yb 3+, elucidating the change in luminescence intensity in terms of microscopic mechanism. All the above results manifest that SBHT- x Yb ceramics are good potential alternative for luminescence and piezoelectric properties integrated devices.